2007
DOI: 10.1073/pnas.0704751104
|View full text |Cite
|
Sign up to set email alerts
|

GTPase acceleration as the rate-limiting step in Arabidopsis G protein-coupled sugar signaling

Abstract: Heterotrimeric G protein signaling is important for cell-proliferative and glucose-sensing signal transduction pathways in the model plant organism Arabidopsis thaliana. AtRGS1 is a seven-transmembrane, RGS domain-containing protein that is a putative membrane receptor for D-glucose. Here we show, by using FRET, that D-glucose alters the interaction between the AtGPA1 and AtRGS1 in vivo. AtGPA1 is a unique heterotrimeric G protein ␣ subunit that is constitutively GTP-bound given its high spontaneous nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
266
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(281 citation statements)
references
References 38 publications
(62 reference statements)
12
266
0
3
Order By: Relevance
“…We purified this protein and measured its nucleotide exchange rate in a fluorescence assay (GTP-bound Gα proteins have higher intrinsic fluorescence than GDP-bound G proteins) (17). Consistent with a previous study (6), wild-type GPA1 had a spontaneous rate of nucleotide exchange that was fast relative to that of wild-type Gα i1 (Fig. 4B).…”
Section: Gpa1 and Gα I1 Exhibit Different Frequencies Of Two-domain Msupporting
confidence: 92%
See 2 more Smart Citations
“…We purified this protein and measured its nucleotide exchange rate in a fluorescence assay (GTP-bound Gα proteins have higher intrinsic fluorescence than GDP-bound G proteins) (17). Consistent with a previous study (6), wild-type GPA1 had a spontaneous rate of nucleotide exchange that was fast relative to that of wild-type Gα i1 (Fig. 4B).…”
Section: Gpa1 and Gα I1 Exhibit Different Frequencies Of Two-domain Msupporting
confidence: 92%
“…We chose to study GPA1 because basal nucleotide exchange is >100-fold faster than that of Gα i1 under optimal conditions for each enzyme (6,8). Despite large differences in activation rates, GPA1 and Gα i1 crystal structures (9,10) show remarkable similarity, with an average root-mean-square deviation of only 1.4 Å in core residue Cα atoms (Fig.…”
Section: Gpa1 and Gα I1mentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotrimeric G-proteins are conserved signaling components across diverse eukaryote species (Jones and Assmann, 2004;Johnston et al, 2007;Jones et al, 2011aJones et al, , 2011b. Upon perception of a cognate ligand by its seven-transmembrane receptor on the cell surface, the seven-transmembrane receptor-associated heterotrimeric G-protein complex dissociates to form an activated Ga-subunit and an obligate Gbg dimer, which in turn trigger transient cellular changes by interacting with downstream proteins, typically enzymes, called effectors.…”
mentioning
confidence: 99%
“…Biochemical analysis suggests that AtGPA1 is a unique heterotrimeric G-protein a-subunit that binds constitutively to GTP. It is suggested that high Glc modulates the GTPase-activating protein activity of AtRGS1 to inhibit AtGPA1 (Johnston et al, 2007). This Glc-sensing mechanism is distinct from the HXK1 pathway.…”
Section: Connecting the Sugar Signaling Networkmentioning
confidence: 99%